Gastroesophageal reflux disease after peroral endoscopic myotomy is unpredictable, but responsive to proton pump inhibitor therapy: a large, single-center study - Nabi, Zaheer; Ramchandani, Mohan; Kotla, Rama; Tandan, Manu; Goud, Rajesh; Darisetty, Santosh; Rao, G. Venkat; Reddy, D. Nageshwar (Endoscopy, 2020)
Background Gastroesophageal reflux disease (GERD) is an important concern after peroral endoscopic myotomy (POEM). However, there are limited data on the risk factors for post-POEM GERD and its responsiveness to proton pump inhibitors (PPIs). In this study, we aimed to analyze the variables affecting the occurrence of GERD and its response to PPI therapy.Methods Consecutive patients with idiopathic achalasia who underwent POEM (December 2016 to January 2018) were evaluated for GERD using 24-hour pH impedance, esophagogastroduodenoscopy (EGD), and symptoms. Multivariate analysis was performed to identify the variables affecting the incidence of post-POEM GERD.Results A total of 209 patients with esophageal motility disorders, including 194 patients with non-sigmoid achalasia, underwent POEM during the study period. Comprehensive evaluation of GERD was completed on 167 patients (86.1 %): 47.3 % women with a mean (standard deviation) age of 41 (14.42) years and body mass index of 22.2 (3.89) kg/m2; the majority (70.7 %) were treatment naïve. A high DeMeester score (> 14.72), reflux esophagitis, and symptomatic GERD were identified in 47.9 %, 41.9 %, and 29.3 % of patients, respectively. On logistic regression analysis, type of achalasia, technique of POEM (anterior vs. posterior), pre- or post-POEM esophageal manometry variables, and patient characteristics were not associated with post-POEM GERD. Erosive esophagitis responded to PPI therapy in the majority of patients (81.4 %).Conclusion The incidence of GERD is high after POEM. Most of the reflux esophagitis is mild and responsive to PPI therapy. There are no procedural or patient-related variables that appear to affect the incidence of post-POEM GERD.